Influence of ultraviolet exclusion and of powdery mildew infection on Sauvignon Blanc grape composition and on extraction of pathogenesis‐related proteins into juice. (3rd March 2015) - Tian, B.; Harrison, R.; Jaspers, M.; Morton, J.
Abstract Background and Aims Ultraviolet (UV) radiation and powdery mildew infection could increase the concentration of phenolic substances and proteins in grape berries. This study investigates the changes in the composition of Sauvignon Blanc grapes in response to UV exclusion and to powdery mildew infection, and any consequential influence on the extraction of pathogenesis‐related (PR) proteins into juice which may influence bentonite requirement for wines. Methods and Results Exclusion of UV and powdery mildew infection treatments was applied to potted grapevines grown in a glasshouse. For all treatments, grape skin, pulp and extracted juice were analysed for the concentration of phenolic substances and proteins. The UV exclusion treatment resulted in a lower concentration of phenolic substances, tannins and PR proteins in grape skin, but had no effect on the PR proteins in pulp. Powdery mildew infection of grapes resulted in a significant increase in PR proteins in grape skin and pulp but had no impact on tannins in skin. A lower concentration of PR proteins was observed in the corresponding juice from the control of the UV exclusion experiment. The significantly higher concentration of PR proteins in grapes from the high powdery mildew infection treatment was reflected in the resultant juice. Conclusions Powdery mildew infection and UV exclusion have a significant impact on the composition of Sauvignon Blanc grapes. The concentration of PR proteins in juice is predominantly determined by their concentration in grape pulp, but their concentration in grape skin and interactions with phenolic substances/tannins during the juicing process may modulate their final concentration in juice. Significance of the Study Pathogenesis‐related proteins are the main cause of haze formation in finished white wine. The findings presented here contribute to an improved understanding of the variable concentration of PR proteins in juice and resultant wine, and hence the variation in bentonite requirement.